(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Today, as a new direction in the study of reproductive problems in obese women, the effect of melatonin on the gonadotropic function of the pituitary gland and the process of ovariogenesis is being widely studied. In addition, obesity, which is a concomitant disease in polycystic ovary syndrome, and its relationship with melatonin secretion are of interest to many today. In this article, we discussed the importance of the above-mentioned problem.